1993
DOI: 10.1093/jmedent/30.2.421
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of Pyriproxyfen and Methoprene on Eggs of Ctenocephalides felis (Siphonaptera: Pulicidae)

Abstract: Adult cat fleas were exposed to residues of pyriproxyfen and methoprene in glass vials, then fed on a cat 24 h later to investigate the mode of action of juvenoid growth regulators on embryonic development in flea eggs. Eggs laid by pyriproxyfen-treated fleas within 70 h after exposure to this juvenoid were often devoid of yolk and frequently collapsed after oviposition. Minimal amounts of yolk were deposited in eggs laid after 70 h, and no blastoderm was formed. These results are significant because both mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 0 publications
4
31
0
2
Order By: Relevance
“…Also IGRs may act as growth distruptor, it interferes with moulting by softening the larval endocuticle through reduction in its chitin content and by hardening of the exocuticle as result of enhanced phenoloxidase activity. These results are in agreement with many investigators, Dulmage, 1971;Ibrahim, 1974;Ascher and Nemny, 1979;Dimetry, et al, 1979;Grosscurt and Anderson, 1980;Radwan, et al, 1980;El-Sayed, 1981;El-Nockrashy, et al, 1986;Lecadet and Martouret, 1987;Marguerre-M and Daniel, 1987;Chilcott and Ellar, 1988;Chung and Cote, 1992;Fisk and Wright, 1992;Tabashnik, 1992;Chandler, 1993;Palma and Meola, 1993;Forrester, 1994;El-Kordy, et al, 1995;Pawar, et al, 1995;Smagghe, et al, 1997;Barker, 1998;Said, 1998 In general, the susceptibility of Spodoptera larvae to Dipel-2X increases when treatment after IGRs. The IGRs+Dipel-2X caused more toxic effect than single treatment with Dipel-2X, it could be concluded that IGRs enhanced the toxicity effect of Dipel-2X.…”
Section: Results and Discussion Toxicity Of Dipel-2x And Three Igrssupporting
confidence: 91%
See 1 more Smart Citation
“…Also IGRs may act as growth distruptor, it interferes with moulting by softening the larval endocuticle through reduction in its chitin content and by hardening of the exocuticle as result of enhanced phenoloxidase activity. These results are in agreement with many investigators, Dulmage, 1971;Ibrahim, 1974;Ascher and Nemny, 1979;Dimetry, et al, 1979;Grosscurt and Anderson, 1980;Radwan, et al, 1980;El-Sayed, 1981;El-Nockrashy, et al, 1986;Lecadet and Martouret, 1987;Marguerre-M and Daniel, 1987;Chilcott and Ellar, 1988;Chung and Cote, 1992;Fisk and Wright, 1992;Tabashnik, 1992;Chandler, 1993;Palma and Meola, 1993;Forrester, 1994;El-Kordy, et al, 1995;Pawar, et al, 1995;Smagghe, et al, 1997;Barker, 1998;Said, 1998 In general, the susceptibility of Spodoptera larvae to Dipel-2X increases when treatment after IGRs. The IGRs+Dipel-2X caused more toxic effect than single treatment with Dipel-2X, it could be concluded that IGRs enhanced the toxicity effect of Dipel-2X.…”
Section: Results and Discussion Toxicity Of Dipel-2x And Three Igrssupporting
confidence: 91%
“…Also IGRs compounds which are considered nowadays one of the mainly component of IPM program term IGRs describe a new class of bio-rational compounds. (Mesbah, et al, 1982;Abdel-Naby, et al, 1990;Palma and Meola, 1993;Pawar, et al, 1995& Shiotsuki, et al, 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence that CGA-255Ј728 stimulated increased activity of the fat body supports the conclusion that the compound functions as a juvenile hormone mimic, because juvenile hormone stimulates vitellogenin production in fat body cells (Rothschild et al 1986). Palma et al (1993) exposed ßeas to residues of pyriproxyfen and methoprene by placing adult ßeas in treated scintillation vials for 24 h. The ßeas were placed on cats, and eggs were collected and sectioned at intervals thereafter. Eggs laid by pyriproxyfen-treated ßeas during the Þrst 70 h after IGR exposure were devoid of yolk and frequently collapsed during oviposition.…”
Section: Discussionmentioning
confidence: 99%
“…When they are applied to the pet animal that serves as a host for the adult ßea, these chemicals are highly effective against eggs either preventing oocyte development in the adult ßea, or killing the embryo or the resulting larva as it develops in the egg (Palma 1990). Riddiford and Williams (1967) were the Þrst to observe the ovicidal effects of juvenile hormone analogs in insects.…”
mentioning
confidence: 99%
“…Zool.VoL58 No,2 (Wood, 1917;Suzuki, 1988;Cosoroaba, 2001;Ezaki et al 2002;Pilarczyk et al 2004;Adachi, 2006 (Zeman and Zelezny, 1985;Zeman et al, 1986;Cooper and Cobb, 1987;Zeman, 1987;Hoglund et al 1995;Beugnet et al 1997;Fiddes et al 2005 (Palma et al 1993). Treat- ExP.…”
Section: Zoologymentioning
confidence: 99%